Integrated network analysis and experimental validation identify CCNA2, CD44, and STAT1 as clinically relevant hub genes in oral squamous cell carcinoma - Bu, Mingyang; Gu, Yue; Meng, Yuhan; Cui, Yunyi; Wu, Qianli; Kong, Yali; Liu, Haoyang; Chen, Yi; Zhang, Jiajun; Guo, Lizhen; Yang, Yakun; Huang, Dongyang; et al. (Frontiers in Molecular Biosciences, 2026)
Oral squamous cell carcinoma remains a major clinical challenge, with only marginal gains in long-term survival due to frequent recurrence, lymphatic dissemination and therapeutic resistance. Robust and biologically grounded molecular determinants are needed to improve tumor characterization and facilitate translational advances. Transcriptomic profiles from GSE30784, GSE9844 and TCGA-HNSC were integrated to identify reproducible dysregulated genes, followed by construction of a high-confidence PPI network for hub gene prioritization. Prognostic and diagnostic relevance was assessed using Kaplan–Meier, Cox regression and ROC analyses. Experimental validation was performed by immunohistochemistry in human OSCC tissues and by qPCR in OSCC cell lines. Cross-cohort integration yielded a reproducible set of DEGs, from which CCNA2, CD44 and STAT1 emerged as network-defined hub genes. All three genes were consistently upregulated across independent cohorts and showed significant prognostic and diagnostic associations. Functional enrichment indicated that these genes are embedded in proliferation-, adhesion- and stress-response–related signaling programs. Experimental assays further confirmed their elevated expression at both transcript and protein levels in OSCC tissues and cell models. CCNA2, CD44 and STAT1 constitute reproducible and functionally anchored hub genes in OSCC, carrying both diagnostic and prognostic implications. These findings substantially refine the molecular understanding of OSCC and provide rational entry points for subsequent mechanistic and translational investigations.